The Relationship Between Diet and Symptoms of Gastritis Disease at the HKBP Balige Nursing Academy - Elfrida Nainggolan (CV. AFDIFAL MAJU BERKAH, 2024)
Diet is a habit of respondents eating daily and assessed how respondents eat breakfast, lunch and dinner and how respondents consume additional food every day. gastritis is an inflammatory process in the mucosal and submucosal layers of the stomach, which develops when the protective mechanism of the mucosa is filled with bacteria or other irritants. This study used an analytic research design with the aim of knowing the relationship between diet and symptoms of gastritis disease at Akper HKBP Balige. The results showed that out of 35 (61.4%) respondents with an irregular diet with gastritis symptoms there were as many as 9 (15.8%) respondents and no gastritis symptoms 26 (45.6%) respondents. Whereas from 22 (38.6%) respondents with a regular diet with gastritis symptoms there were 16 (28.1%) respondents and no gastritis symptoms 6 (10.5%) respondents. After performing the Chi Square statistical test with a confidence level of 0.001 or α: 0.05, the p-value = 0.001. There is a relationship between diet and gastritis symptoms at Akper HKBP Balige.